Assessment of Teachers’ Ability to Develop Hots-Based Test Items: A GRM Analysis - Otaya, Lian Gafar; Yahiji, Kasim; Rasimin, Rasimin; Rahmawati, Rahmawati; Imtihan, Nurul; Muhamad, Norhisham Bin (Jurnal Ilmiah Peuradeun, 2025)
Developing Higher-Order Thinking Skills (HOTS)-based test items is a critical competency for teachers in 21st-century education. However, its implementation remains limited, particularly among Islamic education teachers. This study explores teachers’ ability to participate in the Professional Teacher Education Program under the Indonesian Ministry of Religious Affairs at the State Institute for Islamic Studies (IAIN) Sultan Amai Gorontalo to construct HOTS-based assessments. Utilizing an exploratory, cross-sectional design, the study involved 495 madrasah and Islamic education teachers across Indonesia. Data were collected through document analysis of teacher-developed test items and classroom observations, then analyzed using the Graded Response Model (GRM) in the R program. The findings reveal that most participants demonstrated moderate ability levels in developing HOTS-based test items, with ability scores ranging between –1.00 and 1.00. The study highlights significant challenges in item construction, particularly in aligning cognitive levels with stimulus and question indicators. These results emphasize the need for improved pedagogical training and targeted support to strengthen teachers’ competence in designing cognitively demanding assessments. The study contributes to the global discourse on HOTS-based assessment in religious education and offers practical implications for curriculum design, teacher training, and assessment policy in culturally rooted educational contexts.